Growth Effects of Domestic and Foreign Investment in Emerging Economies: The Nigerian Experience - Osisanwo, Bukonla Grace; Maku, Olukayode Emmanuel (NIU Journal of Humanities, 2021)
This study investigates the effects of domestic and foreign investment on the Nigerian growth within a five-variate autoregressive distributed lag (ARDL) model covering the period from 1981 to 2018. With the aim of controlling the problem of variables omission bias, the study includes some control variables. The finding suggests the presence of a long-run relationship among domestic investment, foreign direct investment (FDI) and economic growth in Nigeria. More specifically, the result shows that FDI does not significantly influence output growth in short-run, albeit FDI’s impact is significant in the long-run. This implies that foreign funds are put into investment that mature within short period and which can easily be repatriated from the country with the profit generated. Thus, there is need for government to ensure fund from foreign investors are channelled to sectors that have long-run linkage with the country’s growth. Also, investment was found to be an important indicator that drives growth in the long-run. It means that government should encourage private investment by creating an enabling environment for investment to thrive. However, the adverse effects of domestic investment on growth in the short-run attest to the crowd-out effects of FDI on domestic investment in the country. The study suggests the need for government to ensure amiable and conducive environment for investors to operate and conduct their day-to-day business activities. Keywords: Domestic investment, FDI, output growth, labour, exchange rate, Nigeria.